2017
DOI: 10.4040/jkan.2017.47.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bullying Experience on Psychological Well-Being Mediated by Conflict Management Styles and Psychological Empowerment among Nursing Students in Clinical Placement: A Structural Equation Modeling Approach

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0)If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. ORIGINAL ARTICLE Effects of Bullying Experience on Psychological Well-Being Mediated by Conflict Management Styles and Psychological Empowerment among Nursing Students in Clinical Placement: A Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Nursing students experienced bullying during practicum might result in feelings of powerlessness and psychological distress (Pryjmachuk, Easton, & Littlewood, 2009). Ren and Kim (2017) found that conflict management styles and psychological empowerment could decrease the negative impacts of bullying on psychological well-being. The situations of school bullying might be different from clinical practicum bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students experienced bullying during practicum might result in feelings of powerlessness and psychological distress (Pryjmachuk, Easton, & Littlewood, 2009). Ren and Kim (2017) found that conflict management styles and psychological empowerment could decrease the negative impacts of bullying on psychological well-being. The situations of school bullying might be different from clinical practicum bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al (2016) had found in their qualitative study seven categories in reference to the consequences associated with harassment: mourning or feeling psychologically affected, feeling angry, frightened or irritated, loss of confidence and self-esteem, as well as decreased ability to learn and care for the patient. Some authors (Geller 2013;Ren & Kim 2017) found in their study that having suffered a harassment experience was significantly related to psychological well-being and that it was also closely related to the ability to handle conflicts and the individual empowerment of each person. In addition, they recorded that when a victim was able to control harassment and respond to it effectively, the variables of empowerment and psychological well-being increased.…”
Section: Bullying Consequencesmentioning
confidence: 99%
“…The various studies show significant differences for the figures of the concepts analysed. For example, many authors rated the low prevalence of bullying between 0.5% and 9% (Cooper et al 2011), medium rates around 50-60% (Birks et al 2017;Palaz 2013), and high rates around 90-95% (Clarke et al 2012;Reem-Mabrouk 2013;Ren & Kim 2017). This variability is probably due to the different perceptions of bullying used in the different studies, or the scale or questionnaire that was used to measure it.…”
Section: Prevalence Of Bullyingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nursing students begin to experience interpersonal conflict when they enter clinical placements with preceptors and other nurses that, if unchecked, can lead to unsafe care, including medication errors [4,6,7,8]. One method of preparing nursing students for clinical placements is utilizing high-fidelity simulations representing specific aspects of nursing care realistically.…”
Section: Introductionmentioning
confidence: 99%